Sexual practice and perception of HIV/AIDS amongst men who have sex with men in Kolkata - Deb Soumya; Dutta Sinjita; Dasgupta Aparajita; Biswas Biswajit (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives: Men who have Sex with Men (MSM) are a vulnerable population and need special attention in the fight against the global pandemic of HIV/AIDS. A study was conducted in an MSM clinic to find out to their varied socio-demographic characteristics, their knowledge and attitude towards HIV/AIDS, and its association with their different sexual practices. Materials and Methods: Descriptive, cross sectional study conducted in an MSM clinic in central Kolkata. Results: A total of 108 MSM were studied over a period of six months. A majority (25%) were students, followed by drivers (22.2%), with mean age being 22.8 years. About 13.9% of them were illiterate and 30.6% of them married. A majority (75%) of the clients were initiated to first sexual act during adolescence. Most (44%) of them had indulged in sexual acts with two/three partners in the past one month. The most common form of sexual act was receptive anal sex (83.3%). The commonest reasons for indulging into such sexual acts with men were increased pleasure to have sex with men and increased sexual urge (38.9% and 27.8%) while 19.4% performed such acts in an intoxicated state. Only 22.2% ever used condom in the last one month during sexual acts. Their knowledge and positive attitude towards HIV/AIDS increased significantly with increase in literacy status ( P less than 0.01). Only 36 (33.3%) knew about HIV transmission through anal route while only 35.2% knew the correct method to use condom. Favorable sexual practices like using a condom or having fewer partners was more among the literates than the illiterates ( P less than 0.05). Alarmingly 44.4% felt that one should have sex without a condom if his sex partner was extremely attractive, 88.9% felt that using a condom was not necessary if his partner was clean and hygienic, 69.4% felt that anal sex is for fun, so no condom is required while 43.5% felt getting HIV was a matter of bad luck. Conclusion: Proper IEC to promote condom use and promotion of safe sexual practice among MSM is the need of the hour.